Development of Virtual Reality simulator, TEVS for Turbine education - Mohd Aswad Othman; Muhammad Afifuddin Salehudin; Mohamad Azrul Shahrani; Iman Hakimi Zainal Abidin (Multidisciplinary Applied Research and Innovation, 2021)
The Turbine Engine Virtual Simulator (TEVS) was created for students in Politeknik Banting Selangor since students are difficult to access to a real turbine engine. The real turbine engine is expensive for study purpose and it is dangerous for the students since it is too complex for the students to do practically. Therefore we would like to propose our project which is Turbine Engine Virtual Simulator to overcome this current problem. The real environment of study about turbine engine is complex and hard for the students, so we created a virtual environment for the student to learn more detail about turbine engine. This project is using SteamVr and Unreal Engine 4 to handle the Virtual Reality environment and Oculus Rift is used for the controlling purpose of movement in the program. The project can make student feel like being in an environment consist of hangar, aircraft, tools crib and others that will allow the users to do practical learning in inspection room and theory learning in virtual class. Our goals are the student learns new information and develops skills. TEVS gives a learner a stake in the outcome by putting the learner into the shoes of a character who needs to overcome a real turbine engine scenario. TEVS can transform the way educational content is delivered. Students can learn from realistic scenarios without the risk of practising an unfamiliar skill in an uncontrolled real-life situation. Furthermore, this innovation is in line with IR4.0 to enhance the leraning process. The technological advancements in IR4.0 consist of 3D Printing, augmented reality, virtual reality, cloud computing, hologram, biometrics, multi-touch LCD screen, internet of things, artificial intelligence, big data and QR-code for educational purposes.